2016
DOI: 10.1097/hjh.0000000000001091
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the impact of hypertension on proteinuria by renal arteriolar hyalinosis in nonnephrotic chronic kidney disease

Abstract: Renal arteriolar hyalinosis may potentiate susceptibility to BP-related glomerular damage in patients with nonnephrotic CKD. Dysregulated afferent arteriolar resistance via arteriolar sclerosis may affect hypertensive renal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In a previous study on patients with IgA nephropathy, including many young patients aged <30 years, we reported that blood pressure-dependent reduction in eGFR was higher among those with renal arteriolar hyalinosis than in those without hyalinosis. 9 Therefore, our findings suggest that renal arterio-arteriolosclerosis should be considered a potential risk factor for renal dysfunction even in younger patients with CKD who may not have hypertension and diabetes mellitus.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…In a previous study on patients with IgA nephropathy, including many young patients aged <30 years, we reported that blood pressure-dependent reduction in eGFR was higher among those with renal arteriolar hyalinosis than in those without hyalinosis. 9 Therefore, our findings suggest that renal arterio-arteriolosclerosis should be considered a potential risk factor for renal dysfunction even in younger patients with CKD who may not have hypertension and diabetes mellitus.…”
mentioning
confidence: 66%
“…The current study's findings have significant clinical relevance considering that hyalinosis may be a marker of disrupted autoregulation of glomerular hemodynamics 8 and may potentiate susceptibility to blood pressure-dependent glomerular damage, 9 which is considered a mechanism of CKD progression. In a previous study on patients with IgA nephropathy, including many young patients aged <30 years, we reported that blood pressure-dependent reduction in eGFR was higher among those with renal arteriolar hyalinosis than in those without hyalinosis.…”
mentioning
confidence: 84%
“…This may be caused in part by a tendency toward more afferent arteriolar hyalinosis with advancing CKD. 29 Mesangial cell contraction caused by RAAS activation leading to a decreased capillary surface area also could contribute to decreased SNGFR without reducing mean GV. 30 Of note, SNUPE was much higher in the ORG subgroups with more advanced CKD stages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even a normal range of systemic blood pressure might be associated with glomerular hypertension and might result in increased proteinuria. We recently reported that hyalinosis in renal arterioles, a potential marker for dysregulation of the autoregulation system, was associated with higher urinary protein levels and greater reductions in eGFR than those seen in patients without hyalinosis, even within the normal range of blood pressure in IgA nephropathy [ 39 ]. Moreover, we reported that uric acid may augment susceptibility for hypertensive glomerular damage in association with evoking renal arteriolopathy in IgA nephropathy [ 40 ].…”
Section: Discussionmentioning
confidence: 99%